Suspected MRI associated burn injuries in dogs - Peyton, Jamie L.; Culp, William T. N.; Larson, Rich; Peters, S. Jason; Toedebusch, Christine M.; Johnson, Eric G. (Frontiers in Veterinary Science, 2026)
Magnetic Resonance Imaging (MRI) is widely utilized in veterinary medicine for its diagnostic accuracy and safety profile. However, thermal injuries secondary to MRI are a significant adverse event that may be under recognized by veterinary clinicians. This study investigates five canine cases of presumed MRI-induced burns with a distinctive linear pattern, ranging from superficial to full-thickness, at a single veterinary institution. The underlying mechanisms for these thermal injuries was most likely resonant circuit heating or the antenna effect, exacerbated by patient positioning and improper insulation of ECG leads. Clinical implications included delayed wound recognition, extended healing times, and substantial complications such as impaired mobility and delayed neurological rehabilitation. The findings underscore the necessity for improved MRI safety protocols, particularly regarding patient monitoring and positioning during MRI procedures in veterinary practice.